2011
DOI: 10.1007/s00335-011-9315-9
|View full text |Cite
|
Sign up to set email alerts
|

The genetic basis of adrenal gland weight and structure in BXD recombinant inbred mice

Abstract: Adrenal gland function is mediated through secreted hormones, which play a vital role in the autonomic and hypothalamic-pituitary-adrenal (HPA)-axis-mediated stress response. The genetic underpinnings of the stress response can be approached using a quantitative trait locus (QTL) analysis. This method has been used to investigate genomic regions associated with variation in complex phenotypes, but it has not been used to explore the structure of the adrenal. We used QTL analyses to identify candidate genes und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 96 publications
1
11
0
Order By: Relevance
“…This was in agreement with what is reported in many animal species including rat (Rosol et al, 2001;Wan Ezumi et al, 2007) and mouse (Di Curzio and Goldowitz, 2011;Monfared et al, 2014). Although physiological studies have shown that the secretion of adrenal chromaffin cell is mediated by cholinergic agonists (Douglas and Poisner, 1965;Unger and Philips, 1983;De Diego, 2010), attempts to develop immunohistochemical markers for the identification of cholinergic neurons have presented several difficulties.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This was in agreement with what is reported in many animal species including rat (Rosol et al, 2001;Wan Ezumi et al, 2007) and mouse (Di Curzio and Goldowitz, 2011;Monfared et al, 2014). Although physiological studies have shown that the secretion of adrenal chromaffin cell is mediated by cholinergic agonists (Douglas and Poisner, 1965;Unger and Philips, 1983;De Diego, 2010), attempts to develop immunohistochemical markers for the identification of cholinergic neurons have presented several difficulties.…”
Section: Discussionsupporting
confidence: 91%
“…It plays a vital role in both the acute and the prolonged mammalian stress responses (Di Curzio and Goldowitz, 2011). In all adult mammals, the adrenal gland comprises the adrenal medulla and three layers of the adrenal cortex that surround the medulla (Deschepper et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(e) Adrenal morphology and total steroid content Adrenal glands were histologically processed using a haematoxylin and eosin (H&E) stain via previously described methods [37]. The area encompassed by each cortical layer (i.e.…”
Section: (D) Adrenal Responsiveness and Behavioural Testingmentioning
confidence: 99%
“…BXD RI mice have been used in quantitative trait locus (QTL) analyses and have been instrumental in identifying relevant chromosomal loci involved in ethanol and stress responses as well as potential candidate genes that underlie these QTLs (Mulligan et al, 2011, 2012, 2006; Belknap & Atkins, 2001; Buck, Metten, Belknap, & Crabbe, 1997; Cook et al, 2015; Hitzemann et al, 2004; Porcu et al, 2011; Wang et al, 2012; Weng, Symons, & Singh, 2009). Furthermore, BXD RI mice have been extensively evaluated for expression differences across a wide variety of brain regions and other organs (Boughter et al, 2012; Di Curzio & Goldowitz, 2011; Jellen et al, 2012; Lu et al, 2008, 2011; Mozhui, Lu, Armstrong, & Williams, 2012; Overall et al, 2009; Parker et al, 2014; Swaminathan, Lu, Williams, Lu, & Jablonski, 2013). The combination of all the data generated using BXD mice provides a powerful collection of resources that can be used to uncover genetic networks involved in complex phenotypes, making them an excellent model system.…”
Section: Introductionmentioning
confidence: 99%